Methods in Designing Literary Book Covers - Saba Sttar Majid; Asst.Prof. Shaimaa Kamil AlWaeli (Genius Journals, 2022)
The designs of literary book covers are represented by their distinctive directive style, starting with the use of appropriate typographical elements and shaping the book cover to be a defining identity for the book in order to express the ideas and topics contained in the novel, as well as the cover’s reliance on the various color values to express the idea, and its aesthetics are derived from it. The nature of the image and the consistency of the typographic units are a basis for achieving the attractive aesthetic values that contribute to arousing joy and suspense, within the cover, as the designer chooses the appropriate method in employing his idea and the typographic units embodied for him on the covers of literary books.
Keywords: Designs; Book Covers; Directing